2020
DOI: 10.1016/j.rxeng.2020.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Managing the pandemic from the radiology department’s point of view

Abstract: The COVID-19 pandemic is forcing our entire society to adopt numerous changes, at least until an effective treatment and/or vaccine becomes widely available. Because COVID-19 is a new disease that has required us to make complex decisions based on scant evidence, the pandemic is having an enormous impact on our health system. Radiology departments play a fundamental role in the management of COVID-19, both in the diagnosis of the disease and in the posterior management of patients. To ensure the saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Few pieces of research are documenting the changes and measures taken regarding education, patient and staff safety, and research within the radiology department. These are mainly published from middle-and high-income countries (8)(9)(10)(11). A study done in a US radiology teaching unit showed that technology integration for distance learning has promise in maintaining the teaching-learning process while applying social distancing.…”
Section: Introductionmentioning
confidence: 99%
“…Few pieces of research are documenting the changes and measures taken regarding education, patient and staff safety, and research within the radiology department. These are mainly published from middle-and high-income countries (8)(9)(10)(11). A study done in a US radiology teaching unit showed that technology integration for distance learning has promise in maintaining the teaching-learning process while applying social distancing.…”
Section: Introductionmentioning
confidence: 99%